In Vitro Evaluation of Cytotoxic Activities of Marketed Herbal Products in Ghana - Sylvester Languon MSc; Isaac Tuffour MPhil; Emmanuel Ekow Quayson BSc; Regina Appiah-Opong PhD; Osbourne Quaye PhD (SAGE Publishing, 2018)
There are numerous herbal products on the Ghanaian market that are purported to cure various ailments, including cancer. However, scientific investigations on efficacy and toxicity of most of these products are not done. The aim of the study was to assess the anticancer potentials of herbal products on the Ghanaian market. Antiproliferative effects of Kantinka BA (K-BA), Kantinka Herbaltics (K-HER), Centre of Awareness (COA), a stomach (STO) and multicancer (MUT) product were evaluated in vitro using liver (Hep G2), breast (MCF-7), prostate (PC-3 and LNCaP), and blood (Jurkat) cancer cell lines. Cytotoxicity of the medicinal products was assessed using tetrazolium-based colorimetric assay, and total phenolic content and antioxidant activity of the products were determined using Folin-Ciocalteau and 1,1-diphenyl-2-picrylhydrazyl (DPPH) assays, respectively. Phytochemical screening resulted in the detection of terpenoids and flavonoids in most of the products, and alkaloids were detected in only MUT. Tannins were absent from all the products. The highest and lowest concentrations of phenolics were recorded for MUT and K-BA, respectively. The highest and lowest antioxidant activities were measured for MUT and K-HER, respectively. Only 2 products (STO and MUT) were cytotoxic to Hep G2 cells; with MUT being the only product that was cytotoxic to MCF-7 cells. All but K-BA were cytotoxic to PC-3 cells, while all products except K-HER were cytotoxic to LNCaP and Jurkat cells. The study thus confirms that the herbal products have selective cytotoxic activities against the tested cancer cell lines. However, comprehensive toxicity studies must be conducted to establish their safety.